Cellulase cross‐linked enzyme aggregates (CLEA) activities can be modulated and enhanced by precipitant selection. Issue 7 (1st February 2017) - Perzon, Alixander; Dicko, Cedric; Çobanoğlu, Özgür; Yükselen, Onur; Eryilmaz, Jitka; Dey, Estera Szwajcer
Abstract: BACKGROUND: Crosslinked enzyme aggregates (CLEA) technology is a rapid and versatile method to produce immobilized enzymes via precipitation and cross‐linking. A direct relationship between CLEA final activity and process parameters is however yet to be clarified. To address the issue, we have used a factorial design to test the formation and optimization of CLEA made from technical grade cellulase (EC 3.2.1.4). Three types of precipitant (ammonium sulfate, polyethylene glycol, tert‐butyl alcohol) were used at varied levels of cross‐linker concentration, cross‐linking time, and temperature. RESULTS: It was found that the CLEAs produced with tert‐butyl alcohol were inactive, whereas the polyethylene glycol‐ and ammonium sulfate‐CLEA, recovered 29 and 17% of the free enzyme activity, respectively. Testing for re‐usability, we observed that the polyethylene glycol‐CLEA maintained 40% of the initial activity after four cycles, in contrast the ammonium sulfate‐CLEA only maintained 10% of its activity after one cycle. CONCLUSION: Our study highlights the importance of evaluating the effect of the precipitant on final CLEA activity rather than re‐solubilized enzyme activity. It was demonstrated that polyethylene glycol, despite not being able to precipitate the enzymes as readily as ammonium sulfate, resulted in better performing CLEA. © 2016 Society of Chemical Industry